OPTIMALISASI KECERDASAN KINESTETIK MELALUI OLAHRAGA DI DESA TAPEN KABUPATEN BANJARNEGARA - Erick Burhaein; Luri Kusuma Wardani; Ika Ayu Cahyaningsih; Erika Trisna Melinda; Heidi Wildan Firmansyach; Chandra ‘Ainun Yaqin; Muhammad Saleh (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Exercise has been known as an effective means of improving an individual's physical and psychological health. Nevertheless, the role of exercise in the development of kinesthetic intelligence, that is, the ability to integrate the mind and body to achieve precise and skilled movements, is often underpaid. This article reviews how exercise not only improves physical fitness but also improves motor coordination and kinesthetic awareness of a person. This article reviews how exercise not only improves physical fitness but also improves motor coordination and kinesthetic awareness of a person. In addition, this article also examines the challenges faced in promoting an active lifestyle in rural settings, such as limited access to sports facilities and lack of awareness of the benefits of exercise for personal and social development. Suggested solutions include improving sports infrastructure, integrating technology in physical activities, and a more holistic approach to education. By combining empirical evidence and practical approaches, this article offers in-depth insights into how sport can be an effective tool to optimize individual kinesthetic intelligence, build healthy communities, and promote social inclusion and equality in access to sporting opportunities. The study focuses on Tapen Village, in Banjarnegara Regency, as a case study to explore the positive impact of participation in sport on the development of kinesthetic intelligence in rural communities. Through an interdisciplinary approach involving education, public health, and social activities, this article highlights local initiatives such as sports tournaments and community fitness programs that have successfully increased community participation in physical activity.